2016
DOI: 10.1002/anie.201608118
|View full text |Cite
|
Sign up to set email alerts
|

Anions Stabilize Each Other inside Macrocyclic Hosts

Abstract: Contrary to the simple expectations from Coulomb's law, Weinhold proposed that anions can stabilize each other as metastable dimers, yet experimental evidence for these species and their mutual stabilization is missing. We show that two bisulfate anions can form such dimers, which stabilize each other with self-complementary hydrogen bonds, by encapsulation inside a pair of cyanostar macrocycles. The resulting 2:2 complex of the bisulfate homodimer persists across all states of matter, including in solution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
133
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 47 publications
13
133
0
Order By: Relevance
“…[27] They are supported by the layered structure (see Figure 2) and the stacking clearly compensates for the anionic repulsive forces.T he situation is similar to that in ILs in which H-bonds can overcome the repulsion between like-charged ions. [28][29][30][31][32][33] TheX -ray structural features are strongly supported by B3LYP/6-311G** and B3LYP-D3/6-311G** calculations on dimers and tetramers of ion-pairs. [34][35][36] Cut-outs of the X-ray structures are used as starting geometry.Only if the dispersion correction is taken into account do the optimized structures resemble the X-ray structures,which are mainly characterized by the stacking between the rings of N-methyl-6-hydroxyquinolinium cations and the hydrogen bond between the hydroxy proton and the sulfonyl oxygen atom (see SI7).…”
Section: Introductionmentioning
confidence: 94%
“…[27] They are supported by the layered structure (see Figure 2) and the stacking clearly compensates for the anionic repulsive forces.T he situation is similar to that in ILs in which H-bonds can overcome the repulsion between like-charged ions. [28][29][30][31][32][33] TheX -ray structural features are strongly supported by B3LYP/6-311G** and B3LYP-D3/6-311G** calculations on dimers and tetramers of ion-pairs. [34][35][36] Cut-outs of the X-ray structures are used as starting geometry.Only if the dispersion correction is taken into account do the optimized structures resemble the X-ray structures,which are mainly characterized by the stacking between the rings of N-methyl-6-hydroxyquinolinium cations and the hydrogen bond between the hydroxy proton and the sulfonyl oxygen atom (see SI7).…”
Section: Introductionmentioning
confidence: 94%
“…10d In 2015, the Das group published a polyammonium-functionalized tripodal receptor capable of encapsulating a hydrogen sulfate dimer. 11 Very recently, Flood 12 reported that their macrocyclic hosts could stabilize a bisulfate dimer via borderline-strong hydrogen bonds, albeit in a 2:2 (receptor-bisulfate) binding stoichiometry. These reports notwithstanding, the rational capture of two sulfate anions (as opposed to hydrogen sulfate) within the same synthetic framework remains an unmet challenge.…”
mentioning
confidence: 99%
“…[6][7][8] Furthermore, ditopic ionophoresh ave the ability to drive ionextractionp rocesses in liquid-liquid biphasic solvents or promote transport across organic membranes. [5,10,[12][13][14][15][16][17][18][19][20] The design of ditopic ionophores typically involves predictions about appropriate combinationso f chemicalg roups capable of acting as electron and/orh ydrogen-bond donors to drive processes of molecular recognition involving cationic and anionic guest species. Anion binding is typically more elusivet han that of cationsa nd constitutes am ore challenging field from the viewpoints of both experimentsa nd computation.…”
Section: Introductionmentioning
confidence: 99%
“…Anion binding is typically more elusivet han that of cationsa nd constitutes am ore challenging field from the viewpoints of both experimentsa nd computation. [5,10,[12][13][14][15][16][17][18][19][20] The design of ditopic ionophores typically involves predictions about appropriate combinationso f chemicalg roups capable of acting as electron and/orh ydrogen-bond donors to drive processes of molecular recognition involving cationic and anionic guest species. [16] Modeling of these materials is acomplext ask that demands ap rofoundu nderstanding of the relevant intra-and intermolecular interactions, steric and conformational effects, and solvent interactions.…”
Section: Introductionmentioning
confidence: 99%